La proporcionalidad de las penas aplicada a los pirómanos responsables del delito de incendio, en áreas que constituyen patrimonio forestal del estado ecuatoriano - Cueva Córdova, Mónica Alexandra (2014)
The thesis that I put to it is a compendium of research results, and provides a brief overview of theories, ideas and concepts about "THE PROPORTION OF PENALTIES APPLIED arsonists RESPONSIBLE FOR CRIME , FIRE IN AREAS WHICH CONSTITUTE FOREST HERITAGE STATE OF ECUADOR . " From the study of doctrine and legal framework under constant fire arising in the forests of Ecuador is analyzed, as this undermines the constitutional provision regarding the Code of Criminal Integral. A detailed study is made as to the main issue in order to identify the shortcomings of these penalties and the need for psychological treatment responsible for the arson arsonist. Also contains valuable practical basis, obtained from the use of surveys and interviews, along with a case study in relation to the constant fires that have occurred in our country. So this legal research has been able to establish that being a lighter penalty, the offender not escarmientan and continue wildfires is causing a number of effects to nature , the environmental situation has come to the author to provide proposal to reform the Code of Integrated Criminal , you destroy , burn , damage or tale in whole or part , forest or other vegetation shall be punished with imprisonment from nine to twelve and to take into account the arsonists to receiving psychiatric and psychological treatments.